International Patients on Operation Vacation: Medical Refuge and Health System Crisis; Comment on "International Patients on Operation Vacation - Perspectives of Patients Travelling to Hungary for Orthopaedic Treatments" - Neil Lunt (Kerman University of Medical Sciences, 2015)
An understanding of patient mobility, international patients and medical tourism includes supply and demand side considerations. As well as micro-level reports of motivation and satisfaction we must acknowledge broader system-level dynamics. Exploring these may unearth more complex geographies of patient travel.